Back Cover: Missing Small‐Bandgap Metallofullerenes: Their Isolation and Electronic Properties (Angew. Chem. Int. Ed. 45/2013). Issue 45 (11th October 2013) - Wang, Zhiyong; Nakanishi, Yusuke; Noda, Shoko; Niwa, Hiroyuki; Zhang, Jinying; Kitaura, Ryo; Shinohara, Hisanori
<x xml:space="preserve">Abstract</x> Small‐bandgap endohedral metallofullerenes are fascinating compounds with exotic physical properties. Unfortunately, they are usually not accessible because of their high chemical instability. In their Communication on page 11770 ff., H. Shinohara et al. describe how the unstable metallofullerenes can be stabilized and readily extracted. This study gives access to a wide variety of missing unconventional metallofullerenes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>